Pengembangan LKPD (Lembar Kerja Peserta Didik) Berbasis AIR (Auditory Intellectualy Repitition) Pada Materi Sistem Gerak Manusia Dikelas XI MIPA SMA Negeri 1 Palopo - khaerati; Martipa (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the results of the development of AIR (Auditory Intellectualy Repetition) based LKPD (student worksheets) on the material of the human movement system class XI MIPA Senior high school number 1 Palopo. This type of research is R&D (Research and Development) research which refers to the development research design of Hannafin and Peck (1988) which consists of three stages namely needs assessment, design stage, and implementation development stage. The results of the study show that the development of AIR (Auditory Intellectualy Repetition) based LKPD (student worksheets ) on the material of the human movement system class XI MIPA 1 Senior High School Number 1 Palopo is stated: (1) valid with an average total validity value 3,7 the percentage value of validity is 92,5% criteria very valid (2) the p ercentage of teacher responses to the AIR (Auditory Intellectualy Repetition) based LKPD (student worksheets) with an average value 3,8 with a percentage value of 95% very partical criteria (3) the percentage of student responses to the AIR (Auditory Intellectualy Repetition) based LKPD (student worksheets) with an average value of 3,32 with a percentage of 83%) partical criteria (4) the percentage value of effevtiveness of the AIR (Auditory Intellectualy Repetition) based LKPD (student worksheets) with an average value of 83,77% very effective criteria. These criteria indicate that development AIR (Auditory Intellectualy Repetition) based LKPD (student worksheets) is valid, practical, and effective.